Aerobic Oxidation of Hydroxymethylfurfural and Furfural by Using Heterogeneous CoxOy–N@C Catalysts. Issue 12 (29th October 2014) - Deng, Jin; Song, Hai‐Jie; Cui, Min‐Shu; Du, Yi‐Ping; Fu, Yao
Abstract 2, 5‐Furandicarboxylic acid (FDCA) is considered to be a promising replacement for terephthalic acid since they share similar structures and properties. In contrast to FDCA, 2, 5‐furandicarboxylic acid methyl (FDCAM) has properties that allow it to be easily purified. In this work, we reported an oxidative esterification of 5‐hydroxymethylfurfural (HMF) and furfural to prepare corresponding esters over CoxOy–N@C catalysts using O2 as benign oxidant. High yield and selectivity of FDCAM and methyl 2‐furoate were obtained under optimized conditions. Factors which influenced the product distribution were examined thoroughly. The CoxOy–N@C catalysts were recycled five times and no significant loss of activity was detected. Characterization of the catalysts could explain such phenomena. Using XPS and TGA, we made a thorough investigation of the effects of ligand and pyrolysis temperature on catalyst activity.